On Interactive Interfaces for Semi-Structured Academic Document Seeking and Relevance Decision Making - Loizides, Fernando; Photiades, Thomas; Mavri, Aekaterini; Zaphiris, Panayiotis (My University, 2014)
The process undertaken by an information seeker, in order to form relevance decisions regarding documents, is defined as “Document Triage.” To better facilitate users’ needs in their triage activities, interactive interfaces have begun to evolve within on-line academic repositories. In order to complement current work on interface design and interaction, and produce custom guidelines to inform the creation of triage interfaces, we examine how interfaces that alter the document presentation and structure affect information seekers’ visual and navigational attention. We present a set of heuristics for both creating and evaluating such interfaces.
Keywords: Information seeking; User interfaces; Document triage; Information interaction; Information architecture